STUDY ON MECHANICAL PROPERTIES OF THE COATING APPLIED BY ELECTROSPARK ALLOYING - Victor Vasilyevich Blazheyev; Pavel Grigoryevich Ivanochkin; Andrey Sergeyevich Lichkovakha (Advanced Engineering Research)
A technique for selecting an electrode material used when applying the electrospark method onto a metal surface layer is described. The technique is based on the study of the mechanical properties of the coating by nanoindentation. The coverage microhardness distribution in depth for a number of the investigated materials is developed. As a second characteristic of the material, the plasticity index reflecting the structural state of the material is used during the indentation. Value H/E is also used to describe the capability of materials to frictional wear. A qualitative comparative characteristic — ratio H3/E2 was used to assess the resistance of materials to plastic deformation. Based on the analysis of the obtained results, a reasonable choice of the electrode material which creates coatings with sufficiently high mechanical properties is made. The relevance of the study is proved by the advantages of the electrospark alloying (ESA) which is an effective method of impact on the surface layers of the various parts.